Neck and Cervical Spine Injuries in National College Athletic Association Athletes: A 5-Year Epidemiologic Study. Issue 1 (1st January 2020) - Deckey, David G.; Makovicka, Justin L.; Chung, Andrew S.; Hassebrock, Jeffrey D.; Patel, Karan A.; Tummala, Sailesh V.; Pena, Austin; Asprey, Walker; Chhabra, Anikar
Abstract : Study Design: Descriptive epidemiology study. Objective: The purpose of this study was to describe the epidemiology of neck and cervical spine injuries in collegiate athletes over a 5-year period. Summary of Background Data: The incidence and etiology of neck and cervical spine injuries in National Collegiate Athletic Association (NCAA) athletes has not been well defined in recent years. Methods: The incidence and characteristics of neck and cervical spine injuries were identified utilizing the NCAA Injury Surveillance Program database. Rates of injury were calculated as the number of injuries divided by the total number of athlete-exposures (AEs). AEs were defined as any student participation in one NCAA-sanctioned practice or competition. Results: Nationally, there were an estimated 11, 510 neck and cervical spine injuries over the 5-year period. These occurred at a rate of 7.05 per 100, 000 athlete-exposures (AEs). The rate of neck and cervical spine injuries in men was 2.66 per 100, 000 AEs, while women suffered injuries at a rate of 1.95 per 100, 000 AEs. In sex-comparable sports, men were 1.36 times more likely to suffer a neck or cervical spine injury compared with women. Men's football (29.09 per 100, 000 AEs) and women's field hockey (11.51 per 100, 000 AEs) were the sports with the highest rates of injuries. These injuries were 3.94 times more likely to occur during competition compared with practice. In-season injury rates were the highest, at 8.18 per 100, 000 AEs. Conclusion: The vast majority of neck and cervical spine injuries in NCAA athletes are minor and uncommon. Across all sports in both sexes, the majority of injuries were new, and occurred during in-season competitions. Most athletes returned to play within 24 hours of injury. These data can inform players, parents, coaches, athletic trainers, and physicians regarding the prevalence and rates of these injuries and potentially inform decision-making regarding injury prevention, treatment, and rehabilitation. Level of Evidence: 4 Abstract : The incidence and etiology of neck and cervical spine injuries in National Collegiate Athletic Association (NCAA) athletes has not been well defined in recent years. The rate of significant and disabling neck and cervical spine injuries appears to be low in NCAA athletes.